(untitled) (Anclajes, 2024)
During the internal armed conflict in Peru (1980-2000) the Andean population endured its worst violence, both by subversive groups and by State agents. Among the other collections of poems that represent the civil war, Rocío Silva Santisteban’s Las hijas del terror stands out in its poeticization of the terror experienced by Andean women victims of sexual violence. This article analyzes four poems from the collection: “Chunniqwasi”, “BAvioLADA”, “Disappeared” and “Las hijas del terror”. It examines, on the one hand, the representation of memory and, on the other, the hierarchies of power that contributed to terror and sexual violence in times of war as well as in times of peace. For our analysis, we employ the concepts of subalternity (Gayatri Spivak), trashization (proposed by Daniel Castillo Durante and studied by Rocío Silva Santisteban), and necropower and necrowriting (Achille Mbembe and Cristina Rivera Garza, respectively). Other important concepts by Marfil Francke, Kimberle Crenshaw and Jelke Boesten on intersectionality and sexual violence help us further the analysis.